A dense plasma focus device as a pulsed neutron source for material identification - Mohamed, Amgad Elsayed Soliman (Kansas State University, 2015)
Dense plasma focus (DPF) devices are pulsed power devices capable of producing short-lived, hot and dense plasmas (~10[superscript]19 cm[superscript]-3) through a fast compression of plasma sheath. A DPF device provides intense bursts of electrons and ion beams, X-rays, and 2.5 MeV neutrons when operated with deuterium through the fusion reaction [superscript]2H(d,n)[superscript]3He. The Kansas State University DPF machine was designed and constructed in early 2010. The device was characterized to determine its performance as a neutron source. The device was shown to produce 5.0x10[superscript]7 neutrons/pulse using a tungsten-copper anode. Such machines have the advantages of being non-radioactive, movable, and producing short pulses (typically tens of nanoseconds), which allows rapid interrogation. The signature-based radiation-scanning (SBRS) method has been used to distinguish targets that contain explosives or explosive surrogates from targets that contain materials called “inert,” meaning they are not explosive-like. Different targets were placed in front of the DPF source at a distance of 45 cm. Four BC-418 plastic scintillators were used to measure the direct neutron yield and the neutrons scattered from various targets; the neutron source and the detectors were shielded with layers of lead, stainless steel, and borated polyethylene to shield against the X-rays and neutrons. One of the plastic scintillators was set at 70[supercript]o and two were set at 110[superscript]o from the line of the neutron beam; a bare [superscript]3He tube was used for detecting scattered thermal neutrons. Twelve metal cans of one-gallon each containing four explosive surrogates and eight inert materials were used as targets. Nine materials in five-gallon cans including three explosive surrogates were also used. The SBRS method indicated a capability to distinguish the explosive surrogates in both experiments, although the five gallon targets gave more accurate results. The MCNP code was used to validate the experimental work and to simulate real explosives. The simulations indicated the possibility to use the time of flight (TOF) technique in future experimental work, and were able to distinguish all the real explosives from the inert materials.
Keywords: Dense Plasma Focus; Material Detection; Neutron Scattering; X-ray Scattering; Nuclear Engineering (0552); Plasma Physics (0759)